PELATIHAN PENGUNAAN E – MODUL BERBASIS STEM PROJECT BASED LEARNING UNTUK MENINGKATKAN BERPIKIR KREATIF PADA SISWA SMP DI KABUPATEN PASURUAN - Rosita Dwi Ferdiani; Wahyudi Harianto (Kanigara, 2023)
This community service activity aims to overcome the problems faced by junior high school students at SMP 1 Purwosari, SMPN 1 Purwodadi, SMPN 1 Sukorejo. The problem faced is that students' creative thinking skills are still low. Teachers rarely give project assignments based on everyday problems associated with one of the subject matter being studied in class, as a result students are less challenged by their creative ideas in completing their assignments. The solution offered is to provide training on the use of E-Module based on STEM Project Based Learning to improve creative thinking for Middle School Students in Pasuruan Regency. Based on the results of the community service activities that have been carried out, it can be concluded that there was an increase in thinking ability which was assessed based on the mathematical test of class VIII students of SMP N 1 Purwodadi, Pasuruan Regency totaling 60 students, indicating that the student's completeness score was 88.44%. Based on the test results of SMPN 1 Purwosari students, the student completeness score was 71.9%. Meanwhile, based on tests at SMPN 1 Sukorejo, it was found that the student's completeness score was 83.26%.